2008
DOI: 10.1177/0091552108319538
|View full text |Cite
|
Sign up to set email alerts
|

Community College Faculty What We Know and Need to Know

Abstract: This review of existing literature about community college faculty members speculates about why they have received so little scholarly attention, summarizes the nature of existing research, including its methodology and topics, and suggests what else needs to be known about them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
75
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 31 publications
1
75
0
Order By: Relevance
“…Around 72 percent of community colleges offer tenure (Twombly and Townsend, 2008), raising the prospect of a thirty-year career at a single institution, which according to Hammons represents a $3 million investment (as cited by Flannigan, Jones, and Moore, 2004). Community college leaders have at least two overlapping considerations when recruiting and hiring faculty: First, community colleges take enormous pride in placing teaching at the heart of their mission; and second, these colleges are strongly committed to an open-door philosophy that welcomes all.…”
Section: Threat or Opportunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Around 72 percent of community colleges offer tenure (Twombly and Townsend, 2008), raising the prospect of a thirty-year career at a single institution, which according to Hammons represents a $3 million investment (as cited by Flannigan, Jones, and Moore, 2004). Community college leaders have at least two overlapping considerations when recruiting and hiring faculty: First, community colleges take enormous pride in placing teaching at the heart of their mission; and second, these colleges are strongly committed to an open-door philosophy that welcomes all.…”
Section: Threat or Opportunitymentioning
confidence: 99%
“…According to Jones-Kavalier and Flannigan (2008), community college leaders express concern "that there are not enough qualifi ed, passionate, and committed people who are willing to apply for full-time positions" (p. 122). Often college students and graduates are either unaware of (Evelyn, 2001;Fugate and Amey, 2000;Murray and Cunningham, 2004) or uninterested (Shoup and Keeler, 2009;Twombly and Townsend, 2008;Winter and Kjorlien, 2000) in a community college teaching career. In a survey of over four thousand doctoral students, Golde and Dore (2001) found that only 3.9 percent aspired to a community college teaching position; 16.6 percent, however, believed that such a career was their likely fate.…”
Section: Threat or Opportunitymentioning
confidence: 99%
“…Citing the Chronicle of Higher Education' s 2005 Almanac, Twombly and Townsend (2008) report that as of the fall 2003 semester, community college professors were 43 percent of all the full-and part-time faculty members in public, nonprofi t postsecondary institutions. The nearly 112,000 full-time faculty members employed by community colleges (U.S. Department of Education, 2007) represent one-fi fth of all faculty members in U.S. higher educational institutions (Twombly, 2005).…”
Section: The Demand For Community College Facultymentioning
confidence: 99%
“…The nearly 112,000 full-time faculty members employed by community colleges (U.S. Department of Education, 2007) represent one-fi fth of all faculty members in U.S. higher educational institutions (Twombly, 2005). Community college instructors, moreover, teach approximately 37 percent of undergraduates-a fi gure that includes nearly 50 percent of all freshmen and sophomores (Twombly and Townsend, 2008). Given their impact on higher education, community colleges and their faculty certainly merit scholarly attention (Twombly and Townsend, 2008).…”
Section: The Demand For Community College Facultymentioning
confidence: 99%
See 1 more Smart Citation